Synthesis of C-Methyl Flavones - G.K, Leong,; Adib A, Mohamed; F, Ahmad (Malaysian Journal of Science, 2005)
Flavonoids possesss interesting biological actions. Some C-alkylated favonoids have been isolated from natural sources. In the present investigation, we have synthesised C-methyl flavones from m-cresol. Acetylationof m-cresol has afforded m-cresyl acetate. Fries rearrangement of m-cresyl acetate with AlCl₃ at 185°C afforded only monoacetyl cresol, which was identified as 2-hydroxy-4-methylacetophenone. Condensation of 2-hydroxy-4-methylacetophenone with anisaldehyde gave 2-hydroxy-4'-methoxy-4-methylchalcone which on oxidative cyclisation with SeO₂ gave 4'-methoxy-7-methylflavone. The structures of the pure compounds were identified by spectroscopic techniques.